STUDI PEMBERIAN EKSTRAK RUMPUT LAUT COKLAT (Sargassum prismaticum) TERHADAP KADAR MDA DAN HISTOLOGI JARINGAN PANKREAS PADA TIKUS Rattus norvegicus DIABETES MELITUS TIPE 1 HASIL INDUKSI MLD-STZ (MULTIPLE LOW DOSE - STREPTOZOTOCIN) - Dewi, Devis Resita; Aulanni'am, Aulanni'am; Roosdiana, Anna (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
The aim of this research was to investigate the effect of brown seaweed (Sargassum prismaticum) extract to decreased MDA levels and improvement of pancreatic tissue histology on rats Rattus norvegicus type 1 diabetes mellitus (DM). Type 1 diabetic rats induced by intraperitonial (i.p) injection of Multiple Low Dose-Streptozotocin (MLD-STZ) with 20 mg/kg (bw) dose for 5 consecutive days. MDA was measured by UV-Vis spectrophotometry method at a wavelength of 540 nm using TBA (Thiobarbituric acid) reagent. Histology of pancreatic tissue performed using Hematoxylen-Eosin staining method. In this research, rats were grouped into 6 treatment groups: the group of control rats, type 1 diabetic rats exposed to MLD-STZ, and type 1 diabetic rats exposed to MLD-STZ than treated by brown seaweed extract orally with 0.8 g/tail dose by 2 mL per day for 1, 3, 5, and 7 days. The results of this research obtained average MDA levels of each group of consecutive treatments were 2.507; 6.770; 5.543; 4.444; 3.734 and 2.980 mg/mL. Therapy with Sargassum prismaticum extract for 7 days can reduce MDA levels of type 1 diabetic rats by 55.98% indicating level of (6.770 ± 0.027) mg/dL to be (2.980 ± 0.017) mg/dL and able to improved pancreatic tissue histology type 1 diabetic rats. Key words: diabetes mellitus, histology, MDA, pancreas, Sargassum prismaticum